Neutrophil recruitment limited by high-affinity bent β2 integrin binding ligand in cis - Zhichao Fan (Nature Portfolio, 2016)
Integrin β2 attachment regulates inflammation via effects on neutrophil rolling and extravasation through sequential integrin extension then headpiece opening. Here the authors show an alternative open headpiece prior to extension stabilized in cisby ICAM-1 that limits neutrophil adhesion.